Numerical investigation of the formation of chemically active components in the spark discharge in water vapors - Vinnikov, D.V.; Korytchenko, K.V.; Sakun, A.V. (Вопросы атомной науки и техники, 2015)
The numerical investigation of the formation of chemically active components and a change in the thermodynamic parameters of the spark discharge at the values of the initial pressure of water vapors 10⁵ and 0.4·10⁵ Pa was carried out. The formation domains of ОН, О, Н, Н2О₂, НО₂, Н₂О components have been determined. It is established that the initial pressure of water vapors produces certain influence on the formation of chemically active components in the spark discharge. Проведено чисельне дослідження напрацювання хімічно активних компонентів і зміни термодинамічних параметрів іскрового розряду при значеннях початкового тиску водяної пари 10⁵ та 0,4·10⁵ Па. Визначено області утворення компонентів ОН, О, Н, Н2О₂, НО₂, Н₂О. Виявлено вплив початкового тиску водяної пари на напрацювання хімічно активних компонентів в іскровому розряді. Проведено численное исследование наработки химически активных компонентов и изменения термодинамических параметров искрового разряда при значениях начального давления паров воды 10⁵ и 0,4·10⁵ Па. Определены области образования компонентов ОН, О, Н, Н2О₂, НО₂, Н₂О. Выявлено влияние начального давления паров воды на наработку химически активных компонентов в искровом разряде.